Color-switchable hybrid dots/hydroxyethyl cellulose ink for anti-counterfeiting applications. (1st January 2021) - Fu, Xijun; Li, Guoqing; Cai, Shaoyong; Yang, Heng; Lin, Kang; He, Miao; Wen, Junwei; Li, Houbin; Xiong, Yabo; Chen, Dongzhi; Liu, Xinghai
Graphical abstract: Highlights: Eco-friendly, color-switchable hybrid dots/hydroxyethyl cellulose ink was explored. Hydroxyethyl cellulose can inhibit aggregation-induced quenching of hybrid dots. 4% hydroxyethyl cellulose imparts the hybrid ink with excellent printability. The hybrid ink endows the covert patterns with impressive dry and wet fastness. Abstract: Many anti-counterfeiting inks have been explored recently, most of them are commonly involved in weak fastness, high cost and long-term toxicity, impeding their real-life applications. Herein, an environment-friendly and inexpensive anti-counterfeiting ink with excellent fastness is reported. The untifake ink is developed by combining hybrid dots (silicon/carbon) with hydroxyethyl cellulose (HEC) binder. Interestingly, the HEC binder can effectively prevent from aggregation-induced quenching of hybrid dots. Subsequently, the customized patterns are successfully transferred onto different surfaces of various substrates including cotton fabric, cellulosic paper, glass, metal, silicon wafer and PET film, using the as-prepared ink by screen-printing technique, exhibiting that the hybrid dots/HEC ink possesses widespread practicability. Notably, fluorescent color of these patterns can be switchable by adjusting environmental pH-value, further imparting the as-prepared ink with excellent covert performance. This new fluorescent hybrid dots/HEC ink will be promising candidates for high-level anti-counterfeiting applications including food packaging, apparel and documents.